2020
DOI: 10.1097/jxx.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a module to promote generic oral contraceptive prescribing among nurse practitioners

Abstract: Although generic oral contraceptives (OCPs) can improve adherence and reduce health care expenditures, use of generic OCPs remains low, and the factors that affect generic prescribing are not well understood. We aimed to understand the barriers and facilitators of generic OCP prescribing and potential solutions to increase generic OCP prescribing, as well as pilot an educational module to address clinician misconceptions about generic OCPs. We developed focus group scripts using the 4D model of appreciative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…investigation, but it is beyond the scope of this study. Past studies have suggested that physicians' and nurse practitioners' perception of generics may vary across different types of pharmaceuticals, as do the perceptions of lay people [20,21]. Our study might indicate that manufacturers could take advantage of such perception of inferior quality of generics to maximize their profits at the expense of society at large.…”
Section: Plos Onementioning
confidence: 62%
“…investigation, but it is beyond the scope of this study. Past studies have suggested that physicians' and nurse practitioners' perception of generics may vary across different types of pharmaceuticals, as do the perceptions of lay people [20,21]. Our study might indicate that manufacturers could take advantage of such perception of inferior quality of generics to maximize their profits at the expense of society at large.…”
Section: Plos Onementioning
confidence: 62%